Gender circuits : bodies and identities in a technological age - Shapiro, Eve (Contemporary sociological perspectives, 2010)
The new edition of Gender Circuits explores the impact of new technologies on the gendered lives of individuals through substantive sociological analysis and in-depth case studies. Examining the complex intersections between gender ideologies, social scripts, information and biomedical technologies, and embodied identities, this book explores whether and how new technologies are reshaping what it means to be a gendered person in contemporary society.